De-Coding Da Vinci: The facts behind the fiction of The Da Vinci Code - Welborn, Amy (Our Sunday Visitor, Inc, 2004)
Here is the only book that addresses the many issues raised by the novel The Da Vinci Code. It uses clear and easy-to-read style to lay out the facts about ancient Christian teaching and history, and point out the many surprising errors about religion, history, and art contained in The Da Vinci
Keywords: Fiction